Accurate dynamical structure factors from ab initio lattice dynamics: The case of crystalline silicon. Issue 5 (18th October 2012) - Erba, Alessandro; Ferrabone, Matteo; Orlando, Roberto; Dovesi, Roberto
Abstract A fully ab initio technique is discussed for the determination of dynamical X‐ray structure factors (XSFs) of crystalline materials, which is based on a standard Debye–Waller (DW) harmonic lattice dynamical approach with all‐electron atom‐centered basis sets, periodic boundary conditions, and one‐electron Hamiltonians. This technique requires an accurate description of the lattice dynamics and the electron charge distribution of the system. The main theoretical parameters involved and final accuracy of the technique are discussed with respect to the experimental determinations of the XSFs at 298 K of crystalline silicon. An overall agreement factor of 0.47% between the ab initio predicted values and the experimental determinations is found. The best theoretical determination of the anisotropic displacement parameter, of silicon is here 60.55 × 10−4 Å2, corresponding to a DW factor B = 0.4781 Å2. © 2012 Wiley Periodicals, Inc.